Perceived customer satisfaction towards Perusahaan Otomobil Kedua Sdn Bhd (PERODUA) products and services / Hashidah Harun - Harun, Hashidah (Faculty of Business and Management, 2009)
This case studies the way in “Perceived Customer Satisfaction towards Perusahaan Otomobil Kedua Sdn Bhd (Perodua) Products and Services”. Customer satisfaction is a function of the discrepancy between a consumer’s prior expectations and his or her perception regarding the purchase. Satisfaction is a major driver of customer retention and loyalty, and therefore achieving high consumer satisfaction is a key goal of practitioners. The elements that contribute in customer satisfaction are product quality, product features, and product design and customer services. The purpose of the study is to explain the importance of understanding customer satisfaction towards products and services of Perodua. For these studies, collection data will use both technique which primary data and secondary data. This study will based on findings such as figures that are related to Perodua sales volume, volume totals industry vehicles and others which are related to customer satisfaction which will help these studies, and there have some recommendations that can help in improving the customer satisfactions on Perodua products and services.